Authentication of Students' Holistic Personality Through Character Education - Nisak, Sayida Khoiratun; Wulandari, Triyana; Othman, Nooraini (CV. Zabags Qu Publish, 2024)
This study sought to ascertain how character education was applied in the development of students' overall personalities. Qualitative research was employed as the method. MTs Nibung Putih and SMPN 21 Sabak were the study's locations. The method in this study is a qualitative method of research. The principal, vice principals, homeroom instructors, and students in the two research locations were the main informants with whom the researchers conducted in-depth interviews to gather primary data for this study. Key informants, including the principal, vice principal, homeroom teacher, teachers, and students, were interviewed in-depth to gather data. The following procedures were used to examine the data: data reduction, data display, and conclusion/ verification drawing. The results lead to the following conclusions: (1) There are two ways for managing character education: internal and external schools; (2) Four pillars teaching and learning activities in the classroom, habituation activities, co-curricular activities, and extracurricular activities can be used to achieve internal school strategies. (3) Parent and community cooperation can be used to achieve external school strategies.